Dynamic Modeling of a Hydraulic Excavator Stick by Introducing Multi-Case Synthesized Load Spectrum for Bench Fatigue Test - Penghui Wang; Qingyi Xiang; Grzegorz Królczyk; Pengmin Lu; Binhua Wang; Zhixiong Li (Machines, 2022)
A multi-case load spectrum compiling method is proposed in this study for dynamic modeling of a hydraulic excavator stick to simplify and accelerate the fatigue bench test. This new method includes a simplified criterion of small-load-omitting threshold based on the principle of invariable fatigue damage, an extreme value inference criterion based on the overflow characteristics of the hydraulic system, and a synthetic extrapolation method under various working conditions. Firstly, a one-dimensional spectrum of a medium-sized excavator stick was compiled. Then, the program load spectrum for the bench fatigue test was obtained by modifying the one-dimensional spectrum based on the damage consistency criterion and the damage equivalent principle. Lastly, the fatigue tests were conducted using the program load spectrum, as well as using the random spectrum. The comparison results demonstrate that the damage location and fatigue life distribution of the stick using these two spectra are generally consistent, with a relative error smaller than 8.8%; however, the proposed program load spectrum can accelerate the test process with less time consuming than that of the random spectrum. As a result, the multi-case load spectrum is feasible and reliable for dynamic modeling of the hydraulic excavator stick in practice.